Trusted virtual machine management model for cloud computing - Zhen-ji ZHOU; Li-fa WU; Zheng HONG; Hai-guang LAI; Cheng-hui ZHENG (Tongxin xuebao)
For virtual machine in cloud computing,the authorization of manager domain is too centralized to be secure,and the strategies of tenants can be easily falsified.In view of the two problems,a trusted virtual machine management Model for cloud computing infrastructure is proposed.The model provides fine grained manager domain of virtual machine in which both managers and tenants are strictly constrained when they operate on other tenant domains.The sensitive code and data in tenant virtual machine cannot be accessed or falsified without permission.The model creates a trustable tunnel between tenant and system domain,and distributes tenant strategies using the tunnel in a secure way.Security analysis and experimental results show the model ensures the security of tenant data and tenant strategies effectively.